Mechanical Properties And Biodegradability Study Of Coconut Shell Powder (Csp) Filled Low Density Polyethylene (Ldpe) Film - Rathanak, P.; Muhammad, Ida Idayu; Rahmat, Abdul Razak (2005)
Lately, a lot of campaigns restrict the use of disposable non-degradable plastic because of its environmental problems. This has generated interest in use of degradable plastics. One of the smart alternative is by utilizing the agricultural waste (agrowaste) such as rice husk, baggase, pineapple leaf, coconut shell powder (CSP) and others as biodegradable initiator (fillers) in the plastic composite. The use of agricultural waste materials as a source of raw materials to the plastics industry not only provides a renewable resource, but also generates a non-food source of economic development for farming and rural areas. The aim of this dissertation is to study the effects of CSP as fillers on the mechanical properties and biodegradability of LDPE plastic film. The LDPE resin and CSP was firstly blended using twin screw extruder before being blown into plastic film. Test specimens were then undergo mechanical testing which included tensile, tear and burst test. Biodegradable test by microbes; Pseudomonas and E-coli is also performed. The integration of CSP has resulted increment in modulus of elasticity, burst strength and biodegradability but reductions of tear strength, tensile strength, and elongation at break. This is due poor adhesion between the polymer and fiber. Further research for the suitable coupling agent should be done to enhance the mechanical properties of the composite. However, coconut shell powder has a great potential as filler in producing biodegradable plastic composite in future.